A 13-year-old Female with Bardet- Biedl Syndrome - A Case Report (Bangladesh Journal of Medicine, 2015)
Bardet Biedl syndrome is a rare disease. A case report is presented here where a 13 years old girl presented with obesity, night blindness, learning difficulties and polydactyly. Obesity and night blindness started from since childhood. Her milestones of development were normal but having some learning difficulties. Her parents are healthy as well as her siblings. On examination she looks apathy, extreme obese, having polydactyly and retinitis pigmentosa and high B.P. On laboratory findings there is only dyslipidaemia. On the basis of clinical features she was diagnosed as a case of Bardet-Biedl syndrome.Bangladesh J Medicine Jan 2015; 26 (1) : 31-34